Magnetic and acoustic properties of CoCr₂S₄ - Felea, V.; Cong, P.T.; Prodan, L.; Gritsenko, Y.; Wosnitza, J.; Zherlitsyn, S.; Tsurkan, V. (Физика низких температур, 2018)
We report results of magnetic and ultrasound studies of the sulfide spinel CoCr₂S₄ , for which the multiferroicity has recently been suggested. Clear anomalies in the magnetic and acoustic properties have been observed at TN = 222 K and in applied magnetic fields evidencing the important role of magnetoelastic interactions in this material. In contrast, no anomalies have been detected at TC = 28 K, where a spontaneous electric polarization and isostructural distortions have been reported. We have extracted the H–T phase diagram of CoCr₂S₄ from our experiments for magnetic fields applied along the <111> direction. We discuss our observations in relation to our earlier results obtained for the oxide multiferroic spinel CoCr₂S₄ .